Associations between socio-demographic factors and body dysmorphic disorder (BDD) among UTAR Kampar undergraduate students - Ng, Jia Poh (2023)
Body dysmorphic disorder (BDD) is a mental disorder when a person is excessively preoccupied with a minor or imagined defect in their appearance until it significantly affects their social functioning. BDD patients can be severely disabled and suicidal. Hence, the complication of BDD should not be underestimated and should be valued by society. Students are the pillar of the nation and play significant roles in the country's development, thus identifying the BDD issues among students is essential. Besides, the association between socio-demographic factors and BDD should be examined to allow the clinician to screen for those who have a high risk of BDD to give the appropriate treatment subsequently. Therefore, a cross-sectional iii study was conducted among 110 undergraduate students who studied at Universiti Tunku Abdul Rahman (UTAR), Kampar to determine the association between socio-demographic factors and BDD. A self administred Body Image Disturbance Questionnaire (BIDQ) was distributed physically to subjects that were selected through convenient sampling method. The obtained information was analyzed using Statistical Package for Social Science (SPSS), version 26.0 software. The chisquare test was used to analyze the association between socio-demographic factors and BDD and the association between gender and body foci of concerns among the respondent. In this study, the prevalence of BDD was 4.5%. No significant association was found between gender, age groups, type of faculties, monthly household income, and marital status with BDD (p>0.05). A strong and significant association was found between body fats (X2 =5.495, p=0.019, Φ=0.224) and height (X2 =5.044, p=0.025, Φ=0.214) with gender. Females were significantly more concern about their body fats whereas males were significantly more worried about their height. The current study may raise social awareness towards BDD so that it can be diagnosed in an early stage and manageable.